SMEs Business Development Strategy for Coffee Shop - Siti Yuningsih; Popong Nurhayati; Sufrin Hannan (Bina Nusantara University, 2026)
The fast proliferation of coffee shops and eateries in Bogor has increased rivalry in this business. This also affects Askara Coffee & Kitchen, making it more difficult to sustain revenue stability and business growth. The purpose of this study is to examine the elements that influence consumer purchase decisions at Askara Coffee & Kitchen, as well as to design methods to stabilize revenue and business growth. This study uses a mixed method, combining quantitative and qualitative approaches. To better understand customer behavior in purchasing decisions, qualitative analysis is carried out using the findings from interviews with informants. Meanwhile, the quantitative analysis is carried out utilizing IPA analysis, value chain analysis, Porter's five forces analysis, IFE matrix, EFE matrix, IE matrix, SWOT analysis, and QSPM matrix to determine the suitable strategic priorities for the organization. The main priority strategy produced is for Askara Coffee & Kitchen to add a new area for the coffee shop to address all the current issues while maintaining the nature-themed coffee shop concept, which will impact the increase in business revenue.